Deportations of Lithuanians into Krasnojarsk region in 1948 - Polianskaja, Jana (Genocidas ir rezistencija, 2008)
According to the 1948 Soviet deportation plans and the deportation quotas set in Moscow, 12,000 families were to be deported. Two lists of deportees were drawn up: the main list and the reserve list. It was planned to send the deported people from the Lithuanian SSR to special exile in Krasnoyarsk region and Yakutia ASSR (6,000 families each) and to employ them in the forest preparation enterprises of the Ministry of Forestry of the USSR. This was in preparation for the future collectivisation of the Lithuanian rural areas. The deportations were only the beginning of suffering of the Lithuanian people. In Siberia, they faced inhuman working and living conditions.